Tingkat Kerusakan Buah Kopi oleh Penggerek Buah Kopi (Hypothenemus hampei) di Desa Watumbelar Kecamatan Lewa Tidahu Kabupaten Sumba Timur - Titik Sri Harini; Zainal Abidin (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2024)
This research aims to determine the level of damage to coffee cherries caused by the coffee berry borer (Hypothenemus hampei) in Watumbelar Village, Lewa Tidahu District, East Sumba Regency, on coffee plantations owned by farmers in Watumbelar Village, Lewa Tidahu District, Sumba Regency. East. The method used in this research is a survey method with direct observation techniques on coffee plants to obtain data on the development of damage intensity and the level of damage caused by coffee berry borers. To observe the intensity of damage, 5 coffee farmers/land owners were determined or selected. The area of each land/coffee plantation used as a sample plot is 1 ha. Observations were carried out using the diagonal method, and each plot consisted of 5 sub plots measuring 5x5m². From the land area/expanse of coffee plantations owned by 5 farmers, the number of all plants as observation samples for each farmer's garden was 25 trees, so the total number of coffee plants observed was 125 trees. Observations were carried out 8 times with an observation interval of 1 time a week, and carried out in the morning (07.00 WITA-finish). Symptoms of coffee fruit damage caused by H. hampei in Watumbelar Village are that the coffee